Khyber, British India's North West Frontier : The Story of An Imperial Migraine - Miller, Charles (London Macdonald and Jane's, 1977)
Lively account of Britain's troubles with Afghanistan and India's Northwest Frontier. Not as comprehensive as Peter Hopkirk's Great Game Trilogy, and Miller's conversational style is a bit excessive, as when he refers to the Mad Mullah's proclamations as "crap" or compares a Pakistani official to Telly Savalas. Miller is to be commended though for his grasp of the ethnic, religious and tribal fault lines in Central Asia
Includes Bibliography and Index.
Keywords: Khyber Pakhtunkhwa (Pakistan) -- History -- Pakistan -- Khyber Pakhtunkhwa